Best Practices for Conducting Interprofessional Team Rounds to Facilitate Performance of the ICU Liberation (ABCDEF) Bundle. Issue 4 (April 2020) - Stollings, Joanna L.; Devlin, John W.; Lin, John C.; Pun, Brenda T.; Byrum, Diane; Barr, Juliana
Abstract : Objectives: Daily ICU interprofessional team rounds, which incorporate the ICU Liberation ("A" for Assessment, Prevention, and Manage Pain; "B" for Both Spontaneous Awakening Trials and Spontaneous Breathing Trials; "C" for Choice of Analgesia and Sedation; "D" for Delirium Assess, Prevent, and Manage; "E" for Early Mobility and Exercise; "F" for Family Engagement and Empowerment [ABCDEF]) Bundle, support both the care coordination and regular provider communication necessary for Bundle execution. This article describes evidence-based practices for conducting effective interprofessional team rounds in the ICU to improve Bundle performance. Design: Best practice synthesis. Methods: The authors, each extensively involved in the Society of Critical Care Medicine's ICU Liberation Campaign, reviewed the pertinent literature to identify how ICU interprofessional team rounds can be optimized to increase ICU Liberation adherence. Results: Daily ICU interprofessional team rounds that foster ICU Liberation Bundle use support both care coordination and regular provider communication within and between teams. Evidence-based best practices for conducting effective interprofessional team rounds in the ICU include the optimal structure for ICU interprofessional team rounds; the importance of conducting rounds at patients' bedside; essential participants in rounds; the inclusion of ICU patients and their families in rounds-based discussions; and incorporation of the Bundle into the Electronic Health Record. Interprofessional team rounds in the ICU ideally employ communication strategies to foster inclusive and supportive behaviors consistent with interprofessional collaboration in the ICU. Patient care discussions during interprofessional team rounds benefit from being patient-centered and goal-oriented. Documentation of ICU Liberation Bundle elements in the Electronic Health Record may help facilitate team communication and decision-making. Conclusions: Conducting high-quality interprofessional team rounds in the ICU is a key strategy to support ICU Liberation Bundle use. Abstract : Supplemental Digital Content is available in the text.